2021
DOI: 10.1590/0074-02760200552
|View full text |Cite
|
Sign up to set email alerts
|

Should COVID-19 be branded to viral thrombotic fever?

Abstract: Coronaviruses can cause a diverse array of clinical manifestations, from fever with symptoms of the common cold to highly lethal severe acute respiratory syndrome (SARS) and middle east respiratory syndrome (MERS). SARS-CoV-2, the coronavirus discovered in Hubei province, China, at the end of 2019, became known worldwide for causing coronavirus disease 2019 . Over one year's time period, the scientific community has produced a large bulk of knowledge about this disease and countless reports about its immune-pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…Severe COVID-19 is characterised by systemic thrombosis, pulmonary venous congestion and embolism. 28 , 29 In addition, several studies have identified D-dimer and coagulation factors as biomarkers of severe disease. 30 , 31 , 32 Herein, we identified high levels of circulating D-dimer associated with anti-NP and anti-RBD IgG only in severely infected patients.…”
Section: Discussionmentioning
confidence: 99%
“…Severe COVID-19 is characterised by systemic thrombosis, pulmonary venous congestion and embolism. 28 , 29 In addition, several studies have identified D-dimer and coagulation factors as biomarkers of severe disease. 30 , 31 , 32 Herein, we identified high levels of circulating D-dimer associated with anti-NP and anti-RBD IgG only in severely infected patients.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular alterations, such as endothelial rupture by direct signaling effects or indirectly by increasing the production of inflammatory mediators accompanied by coagulation cascade dysregulation, have been reported in infections with other coronaviruses [ 55 , 56 ]. In fact, the coagulation phenotype of COVID-19 is so remarkable that it was proposed that this disease should be in fact named as viral thrombotic fever [ 57 ]. Similar to COVID-19, SARS-CoV infection was associated with endothelial dysfunction, thrombotic complications, and hematological manifestations.…”
Section: Effects Of Sars-cov-2 On Neural Endotheliummentioning
confidence: 99%
“…In the recent publication "Should COVID-19 be branded to Viral Thrombotic Fever?," the authors intended to frame COVID-19 in more clinical terminology, making an analogy to Viral Hemorrhagic Fever (VHF). In this article, the authors reported: "We found irrefutable evidence in the current literature that COVID-19 is the first viral disease that can be marketed as a viral thrombotic fever" [5]. Although this is a very categorical statement, considering the small number of studies exclusively dedicated to the characterization of COVID-19 as a thrombotic fever, it is very important to consider this designation.…”
Section: Potential Impact Of Thrombotic Complications On Covid-19 Prognosismentioning
confidence: 99%